The predictive value of serum ox-LDL and 25-(OH)-D levels for cerebral edema in patients with hypertensive cerebral hemorrhage: serum ox-LDL and 25-(OH)-D levels for cerebral edema in hypertensive cerebral hemorrhage - Xu, Chao; Wang, Bo; Liu, Niu; Bao, Lei (Journal of Medical Biochemistry, 2025)
[Objective] To analyze the predictive value of serum oxidation-modified low-density lipoprotein (ox-LDL) and 25-hydroxyvitamin D[25-(OH)-D] levels before minimally invasive hematoma evacuation in patients with hypertensive intracerebral hemorrhage (HICH) for cerebral edema.[Methods] 300 patients with HICH in our hospital from August 2022 to August 2024 were selected as research subjects. Patients were divided into a high-level ox-LDL group (ox-LDL≥50 μg/dL) and a low-level ox-LDL group (ox-LDL
Keywords: Hypertensive cerebral hemorrhage; Minimally invasive hematoma evacuation; Cerebral edema; Oxidized modified low-density lipoprotein; 25-hydroxyvitamin D